2009
DOI: 10.2486/indhealth.47.242
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Feet in Cold Exposure

Abstract: Safety shoes worn in cold climates need to protect the wearer from work hazards while at the same time offering thermal comfort 1) . Ordinary street shoes can do a good job of keeping feet warm and comfortable within a wide temperature range of -5 to +25˚C under normal activities and with the body's own thermal reaction and heat redistribution. However, added moisture at +15 to +20˚C in combination with low activity may easily cause local cold discomfort. Total foot comfort is determined by the interaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 41 publications
(58 reference statements)
4
36
0
1
Order By: Relevance
“…This numbness, likely caused by a combination of trauma, pressure ischemia, and cold, represents neuropraxia of small nerves and affected the subject's ability to sense freezing, thus putting him at risk for injury. 2 Choice of footwear is crucial in an extremely cold climate. The subject chose a lightweight ski touring boot (Dynafit ZZero 4 PX-TF Alpine Touring Boots).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This numbness, likely caused by a combination of trauma, pressure ischemia, and cold, represents neuropraxia of small nerves and affected the subject's ability to sense freezing, thus putting him at risk for injury. 2 Choice of footwear is crucial in an extremely cold climate. The subject chose a lightweight ski touring boot (Dynafit ZZero 4 PX-TF Alpine Touring Boots).…”
Section: Discussionmentioning
confidence: 99%
“…Boots that are large enough to support multiple sock layers and warm air trapping, which improves insulation, seem to be critical in this type of expedition. 2,3 Electric boot warmers are another consideration but require significant battery power, up to 8 batteries a day, and are therefore not feasible on long expeditions. Chemical foot warmers can provide additional external heat, but the extra weight and unpredictable efficacy in extreme cold make these impractical as well.…”
Section: Discussionmentioning
confidence: 99%
“…), but the requirement to maintain the proportionality of footwear in relation to the foot remains utterly crucial. Some types of fashionable footwear serve as accessories to garments, meaning the form of such footwear has importance but does not always fully support the physiological function of the foot (Goonetilleke 1999;Kuklane, 2009;Park, 2012;Staheli, 1991;Tailby, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The electrical resistance of materials can change due to the flexing, contamination and moisture absorption from outside or inside sources. It is suggested that in a warm environment the foot may sweat about 30 g/h, and in some cases even up to 50 g/h [19]. Therefore the situation can change drastically when air between leather fibrils and textile fibres is replaced by moisture.…”
Section: Introductionmentioning
confidence: 99%